Changing Default Ventilator Settings on Anesthesia Machines Improves Adherence to Lung-Protective Ventilation Measures. (April 2018) - Chiao, Sunny S.; Colquhoun, Douglas A.; Naik, Bhiken I.; Ma, Jennie Z.; Nemergut, Edward C.; Durieux, Marcel E.; Blank, Randal S.; Forkin, Katherine T.
Abstract : Perioperative lung-protective ventilation (LPV) can reduce perioperative pulmonary morbidity. We hypothesized that modifying default anesthesia machine ventilator settings would increase the use of intraoperative LPV. Default tidal volume settings on our anesthesia machines were decreased from 600 to 400 mL, and default positive end-expiratory pressure was increased from 0 to 5 cm H2 O. This modification increased mean positive end-expiratory pressure from 3.1 to 5.0 cm H2 O and decreased mean tidal volume from 8.2 to 6.7 mL/kg predicted body weight. Notably, increased adherence to LPV from 1.6% to 23.0% occurred quickly with the rate of increase more than doubling from 1.8% to 3.9% per year.